Analisis Pengaruh Citra Destinasi Wisata, Social Media Marketing dan Fasilitas Wisata terhadap Minat Mengunjungi Wisata di Indonesia - Nia Rifanda Putri; Fauza Afni; Asep Supriadi; Fina Amalia Masri; Edi Rahmat Taufik (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The development of tourism in Indonesia is currently increasingly rapid. The development of the tourism sector provides benefits to many parties, including government, society and the private sector. This is because tourism is a sector that is considered profitable to develop as a promising asset for the surrounding community and the government. This research is quantitative research. This research aims to determine the destination image, social media marketing and tourist facilities that influence interest in visiting tourism in Indonesia. The population and sample in this research were tourist visitors spread across Indonesia and there were 150 respondents. Analysis techniques using SPSS. The results of this research have found that destination image, social media marketing and tourist facilities influence interest in visiting tourism in Indonesia.